Who shows which kind of humor? Exploring sociodemographic differences in eight comic styles in a large Chilean sample. Issue 4 (17th March 2020) - Mendiburo‐Seguel, Andrés; Heintz, Sonja
Abstract : The present study investigates mean‐level differences in eight comic styles (fun, benevolent humor, nonsense, wit, irony, satire, sarcasm, and cynicism) depending on the sociodemographic variables gender, age, education, political spectrum, and religious affiliation. A large and varied Chilean adult sample ( N  = 1, 272, 60.1% women; age M  = 39.94, SD  = 17.33) was recruited in face‐to‐face interviews and online testing. They completed self‐reports of the comic styles (the Comic Style Markers) and sociodemographic variables. Overall, small, but meaningful, differences in comic styles were found for the different sociodemographic groups. Men scored higher than women in all comic styles except for benevolent humor, and six styles decreased with age. Having lower education was associated with more cynicism, while the reverse pattern was found for satire and wit. Religious people showed lower scores in four styles than non‐religious people, and cynicism was higher in those identifying with left wing rather than right‐wing attitudes. The present study thus provides insights into who is more likely to engage in different kinds of humor in their everyday lives.